Neurological assessment in the first two years of life : instruments for the follow-up of high-risk newborns - Cioni, Giovanni; Mercuri, Eugenio (Clinics in developmental medicine, 2007)
The book provides a review of the state of the art of neurological assessment in the first two years of life and identifies the most appropriate instruments for the follow-up of newborns who are at risk of developing neurological abnormalities.